Health Benefits of Yerba Mate Consumption on Cardiovascular Health - Dawid Szczepanek; Katarzyna Szczurek; Krzysztof Świerz; Weronika Wacławik; Anna Szwinge; Julianna Szwancyber; Julia Szafraniec; Natalia Lewoniuk; Mateusz Biesok; Maksymilian Macherski (Nicolaus Copernicus University in Toruń, 2024)
Background: Yerba mate is a Paraguayan kind of herbal tea prepared from the dried and roasted leaves of trees called Ilex paraguariensis St. Hill. It is known for high content of polyphenols, methylxanthines and saponins. According to the studies products rich in those nutrients may have a positive influence on the humans cardiovascular health. Materials and methods: We reviewed publications obtained from PubMed and Google Scholar. Articles were selected based on keywords such "yerba mate'', "Ilex paraguariensis'', "cardiovascular diseases''. For the final analysis, qualified articles were published from 2005 to 2024. Results: Confirming positive impact on serum lipid levels individuals using mate tea. Long - term positive influence on blood pressure. Moreover subjects with obesity took advantages of Yerba beverage by decreasing waist-to-hip ratio. Patients with diabetes were observed to have a significant reduction in fasting plasma glucose level and HbA1c concentration. Conclusions: Most of the cited researches support the hypothesis of benefits coming from drinking mate infusions for patients with elevated lipid serum levels, obesity, high blood pressure and type 2 diabetes mellitus. All of mentioned health issues can lead to the cardiovascular problems therefore using mate infusions can prevent CVDs. Taking everything into consideration, medical professionals might recommend Yerba mate tea for their patients especially as a replacement of a coffee.